SINGLE MINERAL DATING BY THE PB-PB STEP-LEACHING METHOD: ASSESSING THE MECHANISMS - Frei R.; Villa I.M.; Nagler T.F.; Kramers J.D.; Przybylowicz W.J.; Prozesky V.M.; Hofmann B.A.; Kamber B.S. (My University, 1997)
Stepwise Pb-Pb leaching (PbSL) has been successfully used to date rock-forming silicates directly linked to metamorphic reactions defining a PT path. The two features of PbSL are an increase of precision and a control on accuracy: the former, by enhancing the 206Pb/204Pb and207 Pb/204Pb ratios, and the latter, by revealing heterochemical inclusions via the 208Pb/206Pb ratio and checking isotopic equilibrium with the host.The question of the need for inclusions as a prerequisite enabling PbSL dating was investigated on a centimenter-sized single crystal of museum-quality titanite. We obtained petrographic (optical microscope, SEM, electron microprobe, proton microprobe), chemical (ICP-MS), and isotopic (TIMS) data on pristine and increasingly leached splits of different grain sizes, as well as on leach solutions.The PbSL age of 1.00 Ga is identical to the concordant conventional U-Pb age. By use of isotopic and elemental correlation diagrams, we were able to resolve three isotopically distinct sources of Pb. Visible inclusions of K-feldspars as micro-crack fillings may contribute to the first 50% of common Pb (204Pb) release, and visible 5 μm zircons account, at least in part, for the residue. An additional effect noticed during the first leach steps is related to surface hydrolysis and consequent weakening of metal cation-oxygen bonds, which releases structurally bound common Pb substituting for Ca in the titanite lattice. The radiogenic Pb released during most leach steps has uniform 208Pb/206Pb ratios, suggesting that it is derived from a single mineral phase. Further, as different titanite grain sizes produce a different leach trajectory in Pb isotopic space, it can be concluded that this radiogenic Pb is actually derived from the titanite itself. Therefore, PbSL is indeed capable of discriminating common and radiogenic Pb from a single phase.During leaching, a well defined reaction front is seen to advance into the grains. Inside this front, the titanite is unaltered, and outside it, a silica-gel-like rim is formed, in which electron and proton microprobe data show retention of high field strength (HFS) elements. We propose that radiogenic Pb occurs in the tetravalent state (due to recoil stripping) so that it behaves as an HFS element and is preferentially retained in the gel rim during leaching, relative to common divalent Pb. The mechanism by which a spread in Pb isotope data is obtained during PbSL is, therefore, explained by two processes controlling the release of cations from a mineral grain into a leach solution: (1) an effective surface dependent hydrolysis of metal cations at the inward migrating reaction front whose influence decreases as leaching proceeds and (2) an increasingly dominant remobilization of HFS-elements and radiogenic Pb from the micro-environment of the leached gel-like layer which acts as a selective HFS cation absorber. In conclusion, Pb/Pb dating by stepwise leaching can be effective as a dating tool, even in minerals free from micro-inclusions.